2022
DOI: 10.3389/fmicb.2021.745100
|View full text |Cite
|
Sign up to set email alerts
|

Thinned-Young Apple Polyphenols Inhibit Halitosis-Related Bacteria Through Damage to the Cell Membrane

Abstract: The thinned young apple is a by-product and is generally discarded in the orchard during fruit thinning. The polyphenol content of thinned young apples is about 10 times more than that of ripe apples. In our study, the antibacterial effect of thinned young apple polyphenols (YAP) on the halitosis-related bacteria including Porphyromonas gingivalis, Prevotella intermedius, and Fusobacterium nucleatum was investigated. The minimum inhibitory concentrations of YAP against P. gingivalis, P. intermedia, and F. nucl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 57 publications
0
6
0
Order By: Relevance
“…Gram-negative bacteria are reported to be more resistant to polyphenols than gram-positive bacteria [140,148] . The polyphenols from young apple can destroy the integrity and permeability of the cell membrane, leading to bacterial cell death [149] .…”
Section: The Reciprocal Relationship Between Polyphenols and Gut Micr...mentioning
confidence: 99%
“…Gram-negative bacteria are reported to be more resistant to polyphenols than gram-positive bacteria [140,148] . The polyphenols from young apple can destroy the integrity and permeability of the cell membrane, leading to bacterial cell death [149] .…”
Section: The Reciprocal Relationship Between Polyphenols and Gut Micr...mentioning
confidence: 99%
“…These extracts have been found to inhibit the growth of bacteria in the oral cavity and reduce the formation of VSC, addressing the root cause of halitosis. Liu et al found that thinned-young apple polyphenols (YAP) exerted antibacterial effects by destroying the cell membrane of halitosis-related bacteria, including P. gingivalis, P. intermedius, and F. nucleatum [107].…”
Section: Polyphenols and Halitosismentioning
confidence: 99%
“…Young apple polyphenols Polyphenol [94] Bilberry - [78] Cranberry juice Polyphenol Polyphenols damage the bacterial membrane, with changes in permeability, polarization, and interruption in efflux activity. [103] [79]…”
Section: Oxapampa Propolis Flavonoidsmentioning
confidence: 99%